Immersive Virtual Reality and Complex Skill Learning: Transfer Effects After Training in Younger and Older Adults - Dobrowolski, Paweł; Skorko, Maciek; Pochwatko, Grzegorz; Myśliwiec, Monika; Grabowski, Andrzej (Frontiers in Virtual Reality, 2021)
This study investigated the efficacy of training a complex skill within an immersive virtual environment. We constructed a sensorimotor workstation task and trained participants to operate it with either a non-interactive (text, video) method or with a virtual equivalent of the workstation. Our results indicate that virtual reality trained participants had significantly higher accuracy and produced fewer timeouts in the workstation task than those trained using non-interactive methods, demonstrating a successful transfer of skills between virtual reality and the real world. Further, comparing younger and older adults in their performance, we found that older adults did not differ in their ability to benefit from virtual reality training, and that the extent of this benefit was not significantly affected by existing cognitive deficits (as measured using the Operation Span and AX-Continuous Performance tasks). These findings suggest that virtual reality technologies can find application in a wide range of skill training contexts and across diverse age groups.